Synthesis and photostabilizing performance of a polymeric HALS based on 1,2,2,6,6-pentamethylpiperidine and vinyl acetate - Marcelo Aparecido Chinelatto; José Augusto Marcondes Agnelli; Sebastião Vicente Canevarolo (Polímeros, 2015)
Abstract Polymeric hindered amine light stabilizers (polymeric HALS) have been extensively studied because they combine a high ability to protect the polymers against harmful effects of weathering with minimum physical loss. In this study a new polymeric N-methylated HALS was synthesized by the radical copolymerization of a cyclic tertiary amine with vinyl acetate (VAc). 4-Acryloyloxy-1,2,2,6,6-pentamethylpiperidine (APP), the cyclic tertiary amine, was prepared by the initial conversion of 2,2,6,6-tetramethyl-4-piperidinol derivatives via two different routes. The APP/VAc copolymer synthesized was characterized by size exclusion chromatography (SEC), Fourier transform infrared spectroscopy (FTIR) and carbon-13 nuclear magnetic resonance (13C NMR). The photostabilizing performance, particularly the induction period of polypropylene (PP) films containing different concentrations of APP/VAc copolymer, when exposed to accelerated aging, was comparable to that of PP films compounded with commercial polymeric HALS.